Synthesis of Nano-α-Al2O3 for 99Mo Adsorbent - K Kadarisman; S Sriyono; A Abidin; E. Lestari; M Marlina; I. Saptiama; H. Setiawan (Atom Indonesia, 2018)
The fission-product 99Mo, having a high specific activity, is commonly used in alumina-based 99Mo/99mTc generator. Due to the limitation on the use of fission-product 99Mo, an alternative route for 99Mo production, namely activation of natural molybdenum using thermal neutron, has been explored. Unfortunately, this neutron-activated 99Mo has a low specific activity. Therefore, 99Mo/99mTc generator based on neutron-activated 99Mo requires a column with higher capacity absorbent. Thus, in this study, the nanomaterial of alumina (nano-a-Al2O3) was synthesized which was expected to have a higher 99Mo adsorption capacity, so that nano-a-Al2O3 could be potentially used as a matrix of column for 99Mo/99mTc generator based on neutron-activated 99Mo. Nano-a-Al2O3 was synthesized by using sol-gel method and characterized using FTIR spectroscopy, X-ray diffraction (XRD), and transmission electron microscopy (TEM). In addition, the Scherrer method was used to determine the size of the crystals. To determine the 99Mo adsorption capacity of the synthesized nanoalumina, the nano-a-alumina was soaked in nitric acid solution for one hour at room temperature followed by removing the filtrate. Then, the nano-a-alumina was soaked in 99Mo solution (Na299MoO4) at certain conditions. The FTIR spectra for nano-a-alumina showed adsorption peak at 450-500 cm-1 which indicated the presence of Al-O bond. The XRD patterns of nanoalumina crystals showed peaks at 2θ region of 25.8°, 35.9°, 38°, 52.8°, and 57.7°, indicating that the synthesized alumina had an α-phase with an average crystal size of ~5.5 nm. The average 99Mo adsorption capacity of the synthesized alumina was 47.55 ± 12.3 mg Mo/g nano-a-Al2O3.